Residual iris retraction syndrome after artificial iris implantation - Mayer, Christian; Khoramnia, Ramin (American journal of ophthalmology, 2019)
Purpose - To evaluate the effect of an artificial iris implant on the remnant iris. Design - Interventional case series. - Methods - Setting: Single center. Patient Population: Forty-two consecutive patients. Observation Procedures: Morphologic evaluation over 24 ± 14 months. Main Outcome Measures: Remnant pupillary aperture, iris color, visual acuity, intraocular pressure, and endothelial cell count. - Results - In 7 of 42 cases (16.7%), the residual iris aperture dilated from 36.6 ± 15.4 mm2 preoperatively to 61.1 ± 12.5 mm2 1 year postoperatively (66.9% increase). In 5 of 7 affected eyes the artificial iris had been implanted into the ciliary sulcus; in 2 eyes it had been sutured to the sclera. Four of the 7 patients presented with remarkable complications: 2 eyes needed glaucoma shunt surgeries owing to pigment dispersion; 1 suffered from recurrent bleedings; and in 1 case artificial iris explantation was performed owing to chronic inflammation. Anterior chamber depth and angle, endothelial cell count, and visual acuity did not change in this cohort. Changes in color were not observed in the remnant iris. - Conclusions - The implantation of an artificial iris prosthesis can lead to a residual iris retraction syndrome. It is likely that residual iris is trapped in the fissure between the artificial iris and the anterior chamber angle, preventing further pupil constriction. Another possibility could be a constriction or atrophy of the residual iris. A scleral-sutured implant and an implantation in the capsular bag were both found to prevent the iris retraction. The study group number is inadequate to allow statistical comparison of these different implantation methods. As the use of artificial irises increases, we may expect more patients with iris retraction syndrome in the future.